Chart Datum and Bathymetry Correction To Support Managing Coral Grouper In Lepar And Pongok Island Waters, South Bangka Regency - Sudirman Adibrata; Fredinan Yulianda; Mennofatria Boer; I Wayan Nurjaya (Marine Science Department Diponegoro University, 2018)
Corrected bathimetry data is highly required to improve the quality of sea floor map, for a range of purposes including coastal environmental monitoring and management. This research was aimed to know chart datum values used for correctting bathymetry data at Bar-cheeked coral trout grouper (Plectropomus maculates) fishing ground in Lepar and Pongok Island waters 02o57’00”S and 106o50’00”E and 02o53’00”S and 107o03’00”E, respectively, South Bangka Regency, Indonesia. The study was carried out from November 2016 to October 2017, tidal data used for 15 days from September 16–30, 2017 using simple random sampling technique with the total of 845 points of measurements. To calculate tyde harmonic constituents values this study employed admiralty method resulting 10 major components. Results of this research indicated that harmonic coefficient values of M2, M2, S2, N2, K1, O1, M4, MS4, K2, and P1, were 0.0345 m, 0.0608 m, 0.0276 m, 0.4262 m, 0.2060 m, 0.0119 m, 0.0082 m, 0.0164 m, and 0.1406 m, respectively. Values of mean sea level, chart datum, and F, were 0.9620 m, 0.0500 m, and 0.0664 m, respectively, with diurnal type (F= 6.64). Correcting bathymetry values of surveyed location results a deviation about 1.2 m in depth. The calculated chart datum as well as corrected bathymetry provides information that can be used as vertical refrerence datum for generating sea floor map for determining the fishing ground area of bar-cheeked coral trout grouper. Fishing depth usually ranges between 4.2 and 40.8 m. Average water depth in the fishing ground ranged from 14.7 to 22.5 m.